ENHANCING GLOBAL WARMING EDUCATION THROUGH A DISCOVERY LEARNING-BASED HEYZINE FLIPBOOK E-MODULE - Hasibuan, Nurkholijah Rohma; Siagian, Sahat; Tanjung, Samsidar (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research aims to develop a Discovery Learning-based physics E-module using the Heyzine Flipbook platform to improve student learning outcomes on the topic of global warming in Grade X at SMAN 12 Medan. The development model used is the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation, practicality questionnaires for teachers and students, and pretest-posttest evaluations to measure effectiveness. The feasibility test results from content, design, and media experts indicated that the E-module is in the "very feasible" category. The practicality test results showed that both teachers and students considered the E-module easy to use and supportive of the learning process. The effectiveness test using the paired t-test showed a significant improvement in student learning outcomes, while the N-gain analysis indicated a medium category of learning gain. These results demonstrate that the Heyzine Flipbook-based E-module is not only feasible and practical but also effective in enhancing conceptual understanding. The study concludes that the integration of Discovery Learning with digital media can support independent and interactive learning and is recommended for wider implementation across science subjects.